2011
DOI: 10.1016/j.jorganchem.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, properties, and reactivity of carbonylrhodium(I) complexes of di(2-pyrazolylaryl)amido-pincer ligands

Abstract: a b s t r a c tA series of six carbonylrhodium(I) complexes of three new and three previously reported di(2-3R-pyrazolyl)-p-Z/X-aryl)amido pincer ligands, ( R ZX)Rh(CO), (R is the substituent at the 3-pyrazolyl position proximal to the metal; Z and X are the aryl substituents para-to the arylamido nitrogen) were prepared. The metal complexes were studied to assess how their properties and reactivities can be tuned by varying the groups along the ligand periphery and how they compared to other known carbonylrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 87 publications
3
22
0
Order By: Relevance
“…In rhodium chemistry, complexes (Me,Me)Rh(L 1 )(L 2 )(L 3 ) showed ligand-centered oxidations that occurred at potentials that depended on the charge of the complex and the Lever parameter ( E L ) of nonpincer ligands L 1 , L 2 , and L 3 . 19b Also, for a series of carbonylrhodium(I) complexes, (X,Y)Rh(CO), the reactivity toward a given alkyl halide increased predictably with the electron-donating ability of the X and Y groups as indicated by the groups’ Hammett σ p parameter. 19c More recently, the homoleptic gallium(III) complex [Ga(Me,Me) 2 ] + was reported, which showed two reversible one-electron oxidations in its voltammogram.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In rhodium chemistry, complexes (Me,Me)Rh(L 1 )(L 2 )(L 3 ) showed ligand-centered oxidations that occurred at potentials that depended on the charge of the complex and the Lever parameter ( E L ) of nonpincer ligands L 1 , L 2 , and L 3 . 19b Also, for a series of carbonylrhodium(I) complexes, (X,Y)Rh(CO), the reactivity toward a given alkyl halide increased predictably with the electron-donating ability of the X and Y groups as indicated by the groups’ Hammett σ p parameter. 19c More recently, the homoleptic gallium(III) complex [Ga(Me,Me) 2 ] + was reported, which showed two reversible one-electron oxidations in its voltammogram.…”
Section: Introductionmentioning
confidence: 97%
“…19b Also, for a series of carbonylrhodium(I) complexes, (X,Y)Rh(CO), the reactivity toward a given alkyl halide increased predictably with the electron-donating ability of the X and Y groups as indicated by the groups’ Hammett σ p parameter. 19c More recently, the homoleptic gallium(III) complex [Ga(Me,Me) 2 ] + was reported, which showed two reversible one-electron oxidations in its voltammogram. 19a The entire valence series was structurally and spectroscopically characterized.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[22][23][24]40,61 A detailed study dedicated to the search of α 1 -adrenergic receptor agonists among derivatives of 2-(1H-pyrazol-5-yl)-aniline (21) and 2-(1H-1,2,4-triazol-3-yl)aniline (21) was done by Speake. 3 As a result, it was found that these compounds showed high selectivity toward α 1В -and α 1D -receptors.…”
Section: Biological Properties Of 2-(azolyl)anilinesmentioning
confidence: 99%